Identification and Characterization of Progesterone- and Estrogen-Regulated MicroRNAs in Mouse Endometrial Epithelial Cells - Yuan, Dong-zhi (Reprod Sci, 2015)
In endometrial epithelial cells, progesterone (P4) functions in regulating the cell structure and opposing the effects of estrogen. However, the mechanisms of P4 that oppose the effects of estrogen remain unclear. MicroRNAs (miRNAs) are important posttranscriptional regulators that are involved in various physiological and pathological processes. Whether P4 directly induces miRNA expression to antagonize estrogen in endometrial epithelium is unclear. In this study, total RNAs were extracted from endometrial epithelium of ovariectomized mice, which were treated with estrogen alone or a combination of estrogen and P4. MicroRNA high-throughput sequencing with bioinformatics analysis was used to identify P4-induced miRNAs, predict their potential target genes, and analyze their possible biological functions. We observed that 146 mature miRNAs in endometrial epithelial cells were significantly upregulated by P4. These miRNAs were extensively involved in multiple biological processes. The miRNA-145a demonstrated a possible function in the antiproliferative action of P4 on endometrial epithelial cells.